2009
DOI: 10.1158/0008-5472.can-08-2562
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 Impairs Myelopoiesis by Deregulation of PU.1 Function

Abstract: EVI1 is an oncogene inappropriately expressed in the bone marrow (BM) of f10% of myelodysplastic syndrome (MDS) patients. This disease is characterized by severe anemia and multilineage myeloid dysplasia that are thought to be a major cause of mortality in MDS patients. We earlier reported on a mouse model that constitutive expression of EVI1 in the BM led to fatal anemia and myeloid dysplasia, as observed in MDS patients, and we subsequently showed that EVI1 interaction with GATA1 blocks proper erythropoiesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…This scan revealed significant (P < 0.0001) occurrence of 17 TF DNA binding motifs (Table S1). Two TFs previously reported as EVI1 interacting partners, GATA1 (27) and PU.1 (SPI1) (28), were among the overrepresented motifs. When we looked at the sequences of these 17 overrepresented TF motifs, we noticed that several were related to the EVI1 GATA or ETS-like motifs (Table S1).…”
Section: Resultsmentioning
confidence: 87%
“…This scan revealed significant (P < 0.0001) occurrence of 17 TF DNA binding motifs (Table S1). Two TFs previously reported as EVI1 interacting partners, GATA1 (27) and PU.1 (SPI1) (28), were among the overrepresented motifs. When we looked at the sequences of these 17 overrepresented TF motifs, we noticed that several were related to the EVI1 GATA or ETS-like motifs (Table S1).…”
Section: Resultsmentioning
confidence: 87%
“…At diagnosis, there were similar hemoglobin levels or white blood cell counts in both groups. Median platelet counts were 123x10 9 /L, higher than 100x10 9 /L in 53% of EVI1-r AML patients, compared to 25% in the control AML population (P=0.02). These subnormal counts were associated with platelets dysplasia (giant and hypogranular) in 57%.…”
mentioning
confidence: 83%
“…Moreover, it indicates a very low rate of MPO expression in EVI1-r AML patients. It is interesting to note that relationships have been reported between EVI1 expression and MPO regulation, 8,9 suggesting that the translocation could interfere with MPO production in EVI1-r AML. Moreover, a mouse model has shown a relationship between EVI1 and thrombopoiesis, 10 indicating that the peculiar features of EVI1-r AML could be directly related to the abnormal expression of this gene.…”
mentioning
confidence: 99%
“…Several groups reported that Evi1 blocks myeloid differentiation. [11][12][13] Evi1 also affects differentiation of erythroid and megakaryocytic cells. 11,[14][15][16] In addition to its DNA-binding activity, Evi1 has the potential to recruit diverse proteins for transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%